1998
DOI: 10.1074/jbc.273.4.2232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium, Other Ions, and pH on the Reactions of Barley Peroxidase with Hydrogen Peroxide and Fluoride

Abstract: Transient-state kinetic analysis of compound I formation for barley grain peroxidase (BP 1) has revealed properties that are highly unusual for a heme peroxidase but which may be relevant to its biological function. The enzyme shows very little reaction with H 2 O 2 at pH > 5 and exhibited saturation kinetics at higher H 2 O 2 concentrations (k cat app increases from 1.1 s ؊1 at pH 4.5 to 4.5 s ؊1 at pH 3.1 with an enzyme-linked pK a < 3.7 (Rasmussen, C. B., Bakovic, M., Welinder, K. G., and Dunford, H. B. (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…Recent studies with barley peroxidase have suggested that the activity of plant peroxidases may be reversibly controlled by pH and Ca# + -induced conformation changes [27]. Our data show how isotope labelling with %&Ca#+ has potential for kinetic studies of protein folding, such as those with C. cinereus peroxidase [28], which are relevant to the solubilization from inclusion bodies and refolding of variant recombinant peroxidases for academic research and commercial purposes [29,30].…”
Section: Introductionmentioning
confidence: 78%
“…Recent studies with barley peroxidase have suggested that the activity of plant peroxidases may be reversibly controlled by pH and Ca# + -induced conformation changes [27]. Our data show how isotope labelling with %&Ca#+ has potential for kinetic studies of protein folding, such as those with C. cinereus peroxidase [28], which are relevant to the solubilization from inclusion bodies and refolding of variant recombinant peroxidases for academic research and commercial purposes [29,30].…”
Section: Introductionmentioning
confidence: 78%
“…Active Site-Kinetic analysis of BP 1 suggests that BP 1 has a distal histidine in the common arrangement with heme after pH-induced activation (3). The activation has a pK a Ͻ 3.7, and the resultant peroxidase exhibits slow compound I formation with unusual kinetic properties.…”
Section: Distal Domainmentioning
confidence: 99%
“…The possibility of an alternative site of calcium binding with K D ϭ 4 mM leading to a BP 1 with typical peroxidase kinetics is discussed in Ref. 3.…”
Section: Distal Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…In common with other heme-containing peroxidases, BP1 catalyzes the following multistep reaction 271 The rate of the BP1 reaction with hydrogen peroxide is very slow at a pH above 5 and increases as the pH is lowered to 3. At acidic pH, in the presence of calcium ions, the kinetics becomes biphasic 270 and the fast phase behaves like HRPC 272 .…”
Section: Peroxidases (Pr-9)mentioning
confidence: 99%